2017
DOI: 10.1007/s40618-017-0650-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between polycystic ovary syndrome, obesity, and the serum concentration of adipokines

Abstract: While no sufficient evidence is available with regard to the causal association between adipokines and PCOS, they may contribute to the development of PCOS and regarded as the novel biomarkers of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 27 publications
1
26
2
Order By: Relevance
“…The waist circumference and WHR partly reflect the distribution of body fat. The increase in abdominal fat releases a large number of free fatty acids, adipokines and cytokines that are closely related to IR . We did not find any correlation between the hirsutism score or acne score with FIN or HOMA‐IR.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The waist circumference and WHR partly reflect the distribution of body fat. The increase in abdominal fat releases a large number of free fatty acids, adipokines and cytokines that are closely related to IR . We did not find any correlation between the hirsutism score or acne score with FIN or HOMA‐IR.…”
Section: Discussioncontrasting
confidence: 58%
“…The increase in abdominal fat releases a large number of free fatty acids, adipokines and cytokines that are closely related to IR. 19,20 We did not find any correlation between the hirsutism score or acne score with FIN or HOMA-IR. A recent study 21 found that HOMA-IR was positively associated with FG score after adjustments for age, BMI, TT and the number of menses per year.…”
Section: Chinese Pcos Patients By the 'Modified Rotterdam Diagnosticmentioning
confidence: 57%
“…A recent work confirmed that leptin serum concentrations are increased in obese women with PCOS, while adiponectin levels are decreased [94]. Furthermore, the authors suggested the higher leptin levels may be related to the hyperinsulinaemic characteristic of obesity and PCOS [94]. In this sense, as women with PCOS also commonly present overweight and obesity [95], the symptoms mentioned could be a consequence of the hyperleptinaemia due to the gain of fat mass.…”
Section: Leptin and Pathologies Associated With Pregnancymentioning
confidence: 87%
“…Different studies have shown augmented leptin levels in women with PCOS [91][92][93]. A recent work confirmed that leptin serum concentrations are increased in obese women with PCOS, while adiponectin levels are decreased [94]. Furthermore, the authors suggested the higher leptin levels may be related to the hyperinsulinaemic characteristic of obesity and PCOS [94].…”
Section: Leptin and Pathologies Associated With Pregnancymentioning
confidence: 93%
See 1 more Smart Citation